Peran Perilaku Prososial, Efikasi Diri dan Empati pada Pegawai Badan Penanggulangan Bencana Daerah (BPBD) di Bali - A.A. Gd Putra Sastra Pradnyana; Made Diah Lestari (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2017)
Prosocial Behavior is a term of aid behavior which intended to assist people. Prosocial Behavior is an obligation and the main duties of BPBD employee; as it is known that BPBD is enganged in disaster management that emphasizes the humanitarian aspects on the duties or occupation which have been stated in Undang-Undang No 24 Tahun 2007. In carrying out the duties which full of risks and challenges, the employees are required to have the confidence for implementing the capabilities. Furthermore, prosocial behavior is influenced by the empathy to strengthen the help behavior. The research was intended to know the contribution of prosocial behavior, self-efficacy, and empathy in the employee of BPBD in Bali. The subjects of the research were 96 persons; the employees' status are civil servant in BPBD. The research used quantitative approach; in addition, the research instruments were the prosocial behavior scale, self-efficacy scale, and the empathy scale. The analytical method used mutiple regression. R square was 0.414, it was that mean 41% of prosocial behavior can be explained by self-efficacy and empathy. In the regression of t test, it found that standardized empathy coefficient was 0.420. Therefore, the empathy was an independent variable that has the biggest contribution toward prosocial behavior by 42% compared to the contribution of self-efficacy by 31% Keywords: prosocial behavior, self-efficacy, empathy, the employee of BPBD.